Jejak Langkah: “Footsteps” of Pramoedya Studies in China - Lisha, Qie (UPT Pusat Penerbitan LP2MPP ISI Bali, 2025)
Pramoedya Ananta Toer is the most influential literary figure in modern Indonesian literature, with over 50 outstanding literary works that have had a profound impact not only on Indonesian literature but also on the world literary stage. Pramoedya's two visits to China during the 1950s facilitated substantive exchanges with prominent Chinese writers. Pramoedya assimilated conceptual frameworks from China's developmental experience into his intellectual praxis. Simultaneously, engagement with Chinese literary works significantly expanded his creative horizons. Chinese academia has initiated translations of Pramoedya's works as early as the mid-20th century, subsequently developing dedicated research trajectories. This study traces his intellectual engagements in China, examines the historical evolution of Chinese scholarship on his literary works, and analyzes distinctive aspects of Pramoedya studies within China's academic paradigm.